2006
DOI: 10.2337/db05-1359
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-Activated Protein Kinase Within the Ventromedial Hypothalamus Amplifies Counterregulatory Hormone Responses in Rats With Defective Counterregulation

Abstract: Defective counterregulatory responses (CRRs) to hypoglycemia are associated with a marked increase in the risk of severe hypoglycemia. The mechanisms leading to the development of defective CRRs remain largely unknown, although they are associated with antecedent hypoglycemia. Activation of AMP-activated protein kinase (AMPK) in the ventromedial hypothalamus (VMH) amplifies the counterregulatory increase in glucose production during acute hypoglycemia. To examine whether activation of AMPK in the VMH restores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
103
4
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 49 publications
9
103
4
1
Order By: Relevance
“…We have previously shown that pharmacological activation of AMPK in the VMH, using AICAR, led to an amplification of the glucose CRR to acute hypoglycemia in normal Sprague-Dawley rats and in rats with defective counterregulation induced by prior recurrent hypoglycemia (14,15). Although these studies provided support for a role for AMPK in glucose sensing, they were limited by the potential for AICAR to activate other AMP-regulated kinases and/or to act through the adenosine receptor (36).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously shown that pharmacological activation of AMPK in the VMH, using AICAR, led to an amplification of the glucose CRR to acute hypoglycemia in normal Sprague-Dawley rats and in rats with defective counterregulation induced by prior recurrent hypoglycemia (14,15). Although these studies provided support for a role for AMPK in glucose sensing, they were limited by the potential for AICAR to activate other AMP-regulated kinases and/or to act through the adenosine receptor (36).…”
Section: Discussionmentioning
confidence: 98%
“…Hypothalamic AMPK has been implicated in the regulation of food intake (21)(22)(23)(24)(25) and is activated in response to fasting or central glucoprivation (22)(23)(24). Hypothalamic AMPK has also been implicated in the regulation of CRRs to acute hypoglycemia (14,15,26), and 5-aminoimidazole-4-carboxamide-1-␤-D-ribofuranoside (AICAR), a pharmacological activator of AMPK, mimics the effect of low glucose to stimulate neuronal activity in VMH glucose-inhibited neurons (27). Although these studies provide good evidence of a role for AMPK in glucose sensing, they are limited because of the use of pharmacological interventions to manipulate hypothalamic AMPK or having examined for changes in AMPK activity in response to a systemic or intracerebroventricular manipulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5D). The HAAF observed in the SF1-COUP-TFII mice is associated with an overall defective AMPK activation (35).…”
Section: Sf1-coup-tfii Mice Present Hypothalamic Hypersensitivity To mentioning
confidence: 99%
“…As recent antecedent hypoglycemia reduces autonomic (epinephrine) and symptomatic (which normally prompts behavioral defenses such as eating) responses to subsequent hypoglycemia (6,7), a vicious cycle of recurrent hypoglycemia is created where hypoglycemia leads to further impairment of counterregulatory responses, which in turn begets more hypoglycemia and so forth (4,8). Although several mechanisms have been proposed for the development of HAAF, including increased brain glucose transport (9 -11), changes in brain fuel metabolism (12)(13)(14), altered hypothalamic activity (15,16), and changes in brain glucose sensing and signaling (17,18), the exact mechanism underlying this phenomenon is unclear.…”
mentioning
confidence: 99%